Current collector, secondary battery, electric device and preparation method of current collector

CN119816962APending Publication Date: 2025-04-11CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380064388.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-01-18
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In existing secondary batteries, the nucleation overpotential of metal ions on the porous material current collector is large, leading to uneven deposition, easy formation of dendrites, and reduced cycle performance and safety.

Method used

Affinity materials, such as carbon-based materials, non-metal oxides, fluorides, nitrides, sulfides and organic materials, are placed in the pores of porous materials to promote uniform deposition of metal ions, reduce nucleation overpotential and inhibit dendrite formation. generate.

Benefits of technology

It effectively improves the uniform deposition of metal ions, extends the cycle life of the battery, and improves the safety and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816962A_ABST
    Figure CN119816962A_ABST
Patent Text Reader

Abstract

The invention discloses a current collector, a secondary battery, an electric device and a preparation method of the current collector. The current collector comprises: a substrate comprising a porous material; affinity materials are arranged in pores of the porous materials and used for promoting deposition of metal ions in the electrolyte. The affinity material comprises at least one of a carbon-based material, a non-metal oxide, a carbide, a fluoride, a nitride, a sulfide, a phosphide and an organic material. Through the mode, the nucleation overpotential of metal ions on the current collector porous material can be effectively reduced, the uniform diffusion and deposition of the metal ions in the pores of the current collector porous material are promoted, the generation of dendritic crystals is inhibited, and the cycle performance and safety of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Current collector, secondary battery, electrical device, and method for preparing current collector Technical Field

[0001] The present application relates to the field of batteries, and in particular to a current collector, a secondary battery, an electrical device, and a method for preparing the current collector. Background Art

[0002] The cyclability and safety of secondary batteries are closely related to the material and structure of the electrode current collector. Compared with traditional current collectors, porous material current collectors have received increasing attention due to their high specific surface area and multiple nucleation sites. However, the metal ions commonly used in battery electrolytes (such as lithium ions, sodium ions, etc.) have a large nucleation overpotential on conventional porous material current collectors, and are not easy to wet the surface of porous materials. They will preferentially deposit on the surface of porous materials, which may cause the pores inside the porous materials to be blocked and unusable, which is not conducive to the uniform deposition of metal ions in the pores, and is prone to produce dendrites, resulting in a decrease in the cyclability of the battery. In severe cases, dendrites will pierce the diaphragm, causing the battery to short-circuit, affecting the safety performance of the battery.

[0003] Summary of the Invention

[0004] The main technical problem solved by this application is to provide a current collector, a secondary battery, an electrical device and a preparation method of the current collector, which can effectively reduce the nucleation overpotential of metal ions on the porous material of the current collector, promote the uniform diffusion and deposition of metal ions in the pores of the porous material of the current collector, inhibit the formation of dendrites, and improve the cycle performance and safety of the battery.

[0005] In the first aspect, the present application provides a current collector, comprising: a substrate, the substrate comprising a porous material; an affinity material is arranged in the pores of the porous material, and the affinity material is used to promote the deposition of metal ions in the electrolyte; the affinity material comprises at least one of a carbon-based material, a non-metallic oxide, a carbide, a fluoride, a nitride, a sulfide, a phosphide and an organic material.

[0006] In the technical solution of the embodiment of the present application, an affinity material is arranged in the pores of the porous material of the substrate. The affinity material has a high affinity with the metal ions in the electrolyte, which is conducive to promoting the uniform deposition of metal ions in the electrolyte in the pores of the porous material, inhibiting the deposition of metal ions on the surface of the porous material of the current collector, reducing the risk of clogging the pores of the porous material, improving the pore utilization rate of the porous material, reducing the formation of dendrites, and improving the cycle performance and safety of the battery.

[0007] In some embodiments, the carbon-based material includes a heteroatom-doped carbon-based material, which can further enhance the affinity between the affinity material and the metal ions in the electrolyte.

[0008] In some embodiments, the carbon-based material includes at least one of graphite, graphene, graphyne, hard carbon and their derivatives; the aforementioned carbon-based materials are beneficial to reducing the surface energy of the current collector and promoting the nucleation of metal ions on the current collector.

[0009] In some embodiments, the carbon-based material includes at least one of nitrogen-doped graphyne, porous graphene, and graphitized spherical carbon particles. These carbon-based materials are beneficial for reducing the surface energy of the current collector and promoting nucleation of metal ions on the current collector.

[0010] In some embodiments, the oxide includes at least one of graphene oxide and its derivatives. The aforementioned materials are all beneficial in reducing the surface energy of the current collector and promoting the nucleation of metal ions on the current collector.

[0011] In some embodiments, the nitride includes at least one of copper nitride, molybdenum nitride, and derivatives thereof. These materials are beneficial in reducing the surface energy of the current collector and promoting nucleation of metal ions on the current collector.

[0012] In some embodiments, the phosphide includes at least one of copper sulfide, molybdenum sulfide, and derivatives thereof; the aforementioned materials are beneficial for reducing the surface energy of the current collector and promoting the nucleation of metal ions on the current collector.

[0013] In some embodiments, the fluoride includes at least one of copper fluoride, nickel fluoride, magnesium fluoride, and derivatives thereof; the aforementioned materials are all beneficial in reducing the surface energy of the current collector and promoting the nucleation of metal ions on the current collector.

[0014] In some embodiments, the organic material includes at least one of polyvinylidene fluoride, pyrrole, pyridine, polyaniline, and derivatives thereof. These materials are all beneficial in reducing the surface energy of the current collector and promoting nucleation of metal ions on the current collector.

[0015] In some embodiments, the metal ions in the electrolyte include at least one of lithium ions or sodium ions. Lithium ions and sodium ions are common metal ions in battery electrolytes. They have a large nucleation overpotential in porous materials and are not easy to infiltrate the surface of porous materials. They will preferentially deposit on the surface of porous materials, blocking the pores of porous materials and easily forming dendrites. The above method can effectively reduce the nucleation overpotential of lithium ions and sodium ions on the surface and pores of porous materials, significantly improve their uniformity within the pores of porous materials, and inhibit the formation of dendrites.

[0016] In some embodiments, the coating amount of the affinity material is 2-3 g / cm 2 This coating amount will not block the pores of the porous material and hinder the deposition of metal ions in the pores, but will also help improve the uniformity of metal ion deposition.

[0017] In some embodiments, the thickness of the affinity material is 2-20 μm. This thickness range is beneficial for improving the uniformity of the affinity material in the pores of the porous material and reducing the phenomenon of plating leakage, and is also beneficial for reducing the consumption of the deposited layer formed by metal ions during battery discharge and improving the activity of the deposited layer.

[0018] In some embodiments, the porous material includes one or more of copper foam and dealloyed porous copper. On one hand, its large specific surface area helps reduce surface current density and allows for uniform nucleation of metal ions in the electrolyte. On the other hand, its pore structure provides space for metal ion deposition, effectively reducing metal ion deposition on the current collector surface and unlimited volume expansion.

[0019] In some embodiments, the porous material has a pore size of 5-500 μm and a porosity of 30% to 70%. Such pore size and porosity can balance the relationship between the current collector conductivity and the electrolyte ion transport performance, thereby improving the overall performance of the battery.

[0020] In a second aspect, the present application provides a secondary battery comprising a negative electrode, the negative electrode comprising the aforementioned current collector. By forming an affinity material within the pores of the porous material of the negative electrode current collector, metal ions in the electrolyte are facilitated to uniformly deposit within the pores of the negative electrode current collector, thereby reducing the formation of dendrites and improving the battery's cycling performance and safety.

[0021] In some embodiments, the secondary battery is a negative electrode-free secondary battery. Compared to conventional secondary batteries, the secondary battery has a higher energy density, higher safety and stability, and is lighter and smaller in size.

[0022] In some embodiments, the secondary battery further includes an electrolyte, the electrolyte includes metal ions, and the metal ions include at least one of sodium ions or lithium ions.

[0023] On the third aspect, the present application provides an electrical device, including the aforementioned secondary battery, which has good stability and safety in use.

[0024] Fourthly, the present application provides a method for preparing a current collector, comprising: providing a substrate comprising a porous material; and forming an affinity material within the pores of the porous material to obtain the aforementioned current collector. As previously described, the current collector formed by this method has the affinity material within its pores, allowing metal ions in the electrolyte to be uniformly deposited within the pores of the porous material, thereby reducing the formation of dendrites and improving the battery's cycling performance and safety.

[0025] In some embodiments, the current collector preparation method includes: forming an affinity material on a porous material by vapor deposition; and forming an insulating layer on the surface of the porous material to cover the affinity material on the surface of the porous material. Forming the insulating layer on the surface of the porous material can inhibit the deposition of metal ions on the current collector surface, further promoting the deposition of metal ions within the pores of the porous material, and reducing the formation of dendrites.

[0026] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Various other advantages and benefits will become apparent to those skilled in the art upon reading the detailed description of the preferred embodiment below. The accompanying drawings are for illustration purposes only and are not to be considered as limiting the present application. The same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0028] FIG1 is a schematic structural diagram of some embodiments of the secondary battery of the present application;

[0029] FIG2 is a schematic diagram of the exploded structure of some embodiments of the secondary battery of the present application;

[0030] FIG3 is a schematic diagram of the exploded structure of a battery cell according to some embodiments of the present application;

[0031] FIG4 is a schematic structural diagram of a vehicle according to some embodiments of the present application;

[0032] FIG5 is a schematic flow chart of an embodiment of a method for preparing a current collector of the present application;

[0033] FIG6 is a schematic flow chart of another embodiment of the method for preparing the current collector of the present application;

[0034] FIG7 is a morphology diagram of the current collector of Comparative Example 1 of the present application obtained by optical microscope testing;

[0035] FIG8 is a morphology diagram of the current collector of Example 8 of the present application obtained by optical microscope testing;

[0036] FIG9 is a morphology diagram of the current collector of Example 5 of the present application obtained by optical microscope testing;

[0037] FIG10 is a morphology image of the current collector of Example 2 of the present application obtained through an optical microscope test. DETAILED DESCRIPTION

[0038] The following embodiments of the technical solution of the present application will be described in detail with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application and are therefore only examples and are not intended to limit the scope of protection of the present application.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned figure descriptions are intended to cover non-exclusive inclusions.

[0040] In the description of the embodiments of this application, the technical terms "first" and "second" are used only to distinguish different objects and should not be understood to indicate or imply relative importance or implicitly specify the quantity, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "plurality" is more than two, unless otherwise clearly and specifically defined.

[0041] References herein to "embodiments" mean that a particular feature, structure, or characteristic described in connection with the embodiments may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor does it constitute an independent or alternative embodiment that is mutually exclusive of other embodiments. It is understood, both explicitly and implicitly, by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0042] In the description of the embodiments of this application, the term "and / or" is simply a description of the association relationship between associated objects, indicating that three relationships can exist. For example, A and / or B can represent the following three situations: A exists alone, A and B exist simultaneously, and B exists alone. In addition, the character " / " in this document generally indicates that the associated objects are in an "or" relationship.

[0043] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0044] Currently, market developments indicate that power batteries are becoming increasingly widely used. Power batteries are not only used in energy storage systems such as hydropower, thermal, wind, and solar power plants, but are also widely used in electric vehicles such as electric bicycles, electric motorcycles, and electric vehicles, as well as in military equipment and aerospace applications. The cyclability and safety of batteries are closely related to the material and structure of the electrode current collector. Compared to traditional current collectors, porous materials are attracting increasing attention due to their high specific surface area and multiple nucleation sites.

[0045] The inventors have noticed that the nucleation overpotential of metal ions (e.g., lithium ions, sodium ions, etc.) in the battery electrolyte on the porous material current collector is large, making it difficult for them to infiltrate the surface of the porous material. Moreover, when depositing on the porous material, they will preferentially deposit on the surface, resulting in the pores inside the porous material being blocked and the deposition uniformity of the metal ions in the pores being reduced, which can easily lead to the formation of dendrites, which is not conducive to the cycle performance of the battery. Moreover, when dendrites are severe, they can directly pierce the diaphragm and cause the battery to short-circuit, affecting the safety of the battery. The same problem also exists in the process of metal ion embedding and de-embedding in the pores of the porous material.

[0046] In order to alleviate the problem of uneven deposition of metal ions in the electrolyte in the pores of the current collector porous material, the applicant has found that by forming an affinity material with high affinity for metal ions in the pores of the current collector porous material, the nucleation overpotential of the metal ions can be effectively reduced, the uniform diffusion of metal ions in the pores of the porous material can be promoted, the deposition behavior of metal ions can be uniform, the formation of dendrites can be inhibited, and the cycle performance and safety of the battery can be improved.

[0047] Based on the above considerations, in order to solve the problem of uneven deposition of metal ions in the electrolyte within the pores of the current collector porous material, the inventors, after in-depth research, designed a current collector comprising: a substrate comprising a porous material; an affinity material disposed in the pores of the porous material, the affinity material being used to promote the deposition of metal ions in the electrolyte; the affinity material comprising at least one of a carbon-based material, a non-metallic oxide, a carbide, a fluoride, a nitride, a sulfide, a phosphide, and an organic material. Through the above approach, the nucleation overpotential of metal ions on the current collector porous material can be effectively reduced, the uniform diffusion and deposition of metal ions within the pores of the current collector porous material can be promoted, the formation of dendrites can be suppressed, and the cycle performance and safety of the battery can be improved.

[0048] This current collector is used in the positive and / or negative electrodes of secondary batteries. Secondary batteries are batteries that can be recharged after discharge to activate the active materials and continue to be used. By utilizing the reversibility of chemical reactions, chemical energy and electrical energy can be converted to each other, enabling multiple charging and discharging cycles.

[0049] Typically, a secondary battery consists of a positive electrode, a negative electrode, a separator, and an electrolyte. The separator is placed between the positive and negative electrodes to isolate them. The electrolyte conducts ions between the positive and negative electrodes.

[0050] Specifically, in the present application, the substrate of the current collector includes a porous material; an affinity material is provided in the pores of the porous material, and the affinity material is used to promote the deposition of metal ions in the electrolyte; the affinity material includes at least one of a carbon-based material, a non-metallic oxide, a carbide, a fluoride, a nitride, a sulfide, a phosphide and an organic material.

[0051] A current collector is a structure in a battery that collects current. Its primary function is to collect the current generated by the battery's active materials to form a larger current for external output. This includes both positive and negative current collectors. Current collectors can be selected from aluminum, copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, polymer substrates coated with conductive metals, and combinations thereof.

[0052] According to some embodiments of the present application, the substrate of the current collector includes a porous material, which refers to a current collector material having a regular or irregular three-dimensional pore structure. The porous material includes one or more of foamed copper and dealloyed porous copper.

[0053] Copper foam is a new multifunctional material with a large number of connected or unconnected pores evenly distributed in a copper matrix, and has excellent conductivity and ductility.

[0054] Dealloyed porous copper refers to nanoporous copper materials prepared by dealloying process.

[0055] On the one hand, the porous material has a large specific surface area, which helps reduce the surface current density and allows for uniform nucleation of metal ions in the electrolyte. On the other hand, its pore structure leaves space for metal ion deposition, effectively reducing metal ion deposition on the current collector surface and unlimited volume expansion.

[0056] According to some embodiments of the present application, the porous material may also include porous carbon-based materials, etc.

[0057] According to some embodiments of the present application, the pore size of the porous material is 5-500 μm, for example, the pore size of the porous material can be 5 μm, 10 μm, 20 μm, 50 μm, 100 μm, 150 μm, 200 μm, 300 μm, 400 μm, 450 μm, 500 μm, etc., or a range consisting of any two of the above values, for example, 5-200 μm, 400-500 μm, 300-400 μm, 200-400 μm, etc. The porosity of the porous material is 30%-70%, for example, 30%, 35%, 40%, 50%, 60%, 65%, 70%, etc., or a range consisting of any two of the above values, for example, 30%-40%, 50%-70%, 40%-65%, 30%-60%, 65%-70%, etc.

[0058] Pore ​​size refers to the average radius of the pores in a porous material. As you can imagine, pore cross-sections are often irregular, not necessarily perfectly circular. Pore cross-sections are often considered circular, and their size is expressed in terms of radius.

[0059] Porosity refers to the volume fraction of pores in a porous material.

[0060] The pore size and porosity in this application are measured using the pressure pump method.

[0061] The above-mentioned pore size and porosity can not only increase the amount of metal ions deposited in the pores and improve the conductivity of the current collector, but also facilitate the smooth movement of electrolyte ions in the pores and improve the uniformity of deposition, thereby balancing the relationship between the conductivity of the current collector and the ion transport performance of the electrolyte and improving the overall performance of the battery.

[0062] Affinity materials refer to materials that have a high affinity with metal ions in the electrolyte. The metal ions have more active deposition sites on the affinity materials than on the porous material skeleton. Affinity materials can reduce the nucleation overpotential of metal ions on the porous material.

[0063] Metal ions refer to the metal cations of metal salts used to provide current in the electrolyte, such as lithium ions, sodium ions, etc.

[0064] In this embodiment, an affinity material is provided in the pores of the porous material of the substrate, and the affinity material has a high affinity with the metal ions (e.g., lithium ions, sodium ions, etc.) in the electrolyte. The affinity material in the pores of the porous material can attract the metal ions in the electrolyte into the pores, promote the uniform deposition of the metal ions in the pores of the porous material, inhibit the deposition of metal ions on the surface of the current collector and block the pores, inhibit the formation of dendrites, and improve the cycle performance and safety of the battery. Similarly, the affinity material is also conducive to promoting the embedding and de-embedding process of metal ions in the pores of the porous material.

[0065] According to some embodiments of the present application, the carbon-based material includes a heteroatom-doped carbon-based material, wherein the heteroatom may be at least one of oxygen, nitrogen, boron, phosphorus, and sulfur.

[0066] Heteroatom-doped carbon-based materials can reduce the nucleation overpotential of metal ions in electrolysis, further enhancing the affinity between the material and the metal ions in the electrolyte. This is because the doped atoms interact with adjacent carbon atoms in the carbon-based material to form electronegative sites that can act as Lewis bases. These electronegative sites strongly interact with metal cations such as lithium ions.

[0067] According to some embodiments of the present application, the carbon-based material includes at least one of graphite, graphene, graphyne, hard carbon, and their derivatives; and / or the carbon-based material includes at least one of nitrogen-doped graphyne, porous graphene, and graphitized spherical carbon particles. These carbon-based materials can effectively reduce the surface energy of the current collector and promote nucleation of metal ions on the current collector.

[0068] According to some embodiments of the present application, the oxide includes at least one of graphene oxide and its derivatives; and / or the nitride includes at least one of copper nitride, molybdenum nitride, and their derivatives; and / or the phosphide includes at least one of copper sulfide, molybdenum sulfide, and their derivatives; and / or the fluoride includes at least one of copper fluoride, nickel fluoride, magnesium fluoride, and their derivatives; and / or the organic material includes at least one of polyvinylidene fluoride, pyrrole, pyridine, polyaniline, and their derivatives. The aforementioned materials can effectively reduce the surface energy of the current collector and promote the nucleation of metal ions on the current collector.

[0069] According to some embodiments of the present application, the affinity material may further include at least one of a metal material and a metal oxide.

[0070] According to some embodiments of the present application, the metal material includes an element capable of forming an alloy with the metal ions in the electrolyte; and / or, the metal material includes an element capable of forming a solid solution with the metal ions in the electrolyte.

[0071] A solid solution is a solid solution of two or more metals that not only dissolve in each other when molten but also remain mutually soluble upon solidification. After the solid solution transforms into a solid state, it retains its structural uniformity and the lattice type of the solvent metal, allowing the solute metal to be distributed within the solvent metal's lattice. This ordered solid solution structure generally increases the material's hardness and strength, while also reducing its electrical resistance.

[0072] After the metal ions form an alloy with the metal material in the affinity material, the diffusion rate and diffusion uniformity of the metal ions in the pores of the porous material can be further improved because the diffusion rate of the metal ions in the alloy is greater than the self-diffusion rate of the metal ions. At the same time, when the porous material current collector is used for the negative electrode, the formation of the alloy can also increase the negative electrode potential, help improve the quality of the SEI film (Solid Electrolyte Interface) on the negative electrode surface, and help improve the cycle stability of the battery. After the metal ions form a solid solution with the metal material, the distribution uniformity can be further improved and the surface morphology can be improved. The formation of a solid solution can effectively avoid the alloy pulverization caused by the alloy volume change caused by the peeling of the metal ion deposition layer during the battery cycle charge and discharge process, improve the strength and hardness of the affinity material, stabilize the structure of the affinity material, and improve the battery cycle stability.

[0073] According to some embodiments of the present application, the metal material includes at least one of Sn (tin), Mg (magnesium), Zn (zinc), Bi (bismuth), Pb (lead), Au (gold), Ag (silver), Al (aluminum), Si (silicon), In (indium), Ga (gallium) and their alloys.

[0074] The aforementioned metal materials have a high affinity for metal ions commonly used in battery electrolytes, such as sodium and lithium ions. Preferably, the metal material comprises at least one of Mg, Sn, and Zn. More preferably, the metal material comprises at least one of Mg and Zn. More preferably, the metal material comprises Mg, which can form a solid solution with metal ions in the electrolyte, and the structure of the Mg-affinity material is more stable. Mg has similar properties to sodium and lithium ions, so using a Mg-affinity material can form a more uniform deposited layer.

[0075] According to some embodiments of the present application, the metal oxide includes at least one of copper oxide, zinc oxide, magnesium oxide, antimony oxide, and derivatives thereof.

[0076] According to some embodiments of the present application, the metal ions in the electrolyte include at least one of lithium ions or sodium ions.

[0077] Lithium and sodium ions are common metal ions in battery electrolytes. Their nucleation overpotential is high in porous materials, making them less likely to infiltrate the surface. Instead, they preferentially deposit on the surface, clogging the pores and easily forming dendrites. The above method can effectively reduce the nucleation overpotential of lithium and sodium ions on the surface and in the pores of porous materials, improving their uniformity within the pores and inhibiting the formation of dendrites.

[0078] According to some embodiments of the present application, the coating amount of the affinity material is 2-3 g / cm 2 . For example, it can be 2.2g / cm 2 , 2.3g / cm 2 , 2.4g / cm 2 , 2.5g / cm 2 , 2.6g / cm 2 , 2.7g / cm 2 , 2.8g / cm 2 , 2.9g / cm 2 , 3g / cm 2 etc., or a range consisting of any two of the above values. For example, it can be 2-2.3 g / cm 2 , 2.2-2.5g / cm 2 , 2.4-2.7g / cm 2 , 2.3-2.9g / cm 2 , 2.6-3g / cm2 wait.

[0079] This coating amount will not block the pores of the porous material and hinder the deposition of metal ions in the pores, but will also help improve the uniformity of metal ion deposition.

[0080] According to some embodiments of the present application, the thickness of the affinity material is 2-20 μm. For example, it can be 2 μm, 2.5 μm, 3 μm, 5 μm, 10 μm, 15 μm, 19 μm, 20 μm, or a range consisting of any two of the above values, for example, 2-3 μm, 3-5 μm, 10-20 μm, 15 μm-19 μm, etc. This thickness range is beneficial for improving the uniformity of the affinity material within the pores of the porous material and reducing the phenomenon of plating leakage. It is also beneficial for reducing the consumption of the deposited layer formed by metal ions during battery discharge, thereby improving the activity of the deposited layer.

[0081] The present application also provides a secondary battery comprising a negative electrode, the negative electrode including the aforementioned current collector. By forming an affinity material within the pores of the porous material of the negative electrode current collector, metal ions in the electrolyte are facilitated to uniformly deposit or embed within the pores of the porous material of the negative electrode current collector, thereby reducing the formation of dendrites and improving the cycle performance and safety of the secondary battery.

[0082] In one embodiment, the secondary battery is a negative electrode-free secondary battery. Wherein, the negative electrode-free means that in the initial state, the negative electrode structure only includes a current collector and no active material. After the first charge is completed, the metal in the positive electrode material migrates to the surface of the negative electrode current collector, and a metal layer is formed on the negative electrode current collector. During the charging process, the metal electrolyte ions in the electrolyte combine with electrons on the surface and / or in the pores of the negative electrode current collector, and deposition occurs. During the discharge process, the deposited layer on the surface of the negative electrode current collector peels off and dissolves back into metal electrolyte ions and electrons, returning to the positive electrode, and so on. Compared with traditional secondary batteries, the energy density of negative electrode-free secondary batteries is further improved, the safety and stability are also better, and the weight and volume are smaller.

[0083] Because the negative electrode surface does not contain active materials, the nucleation overpotential of the metal ions in the electrolyte at the negative electrode is large, and it is not easy to infiltrate the negative electrode current collector, and it is easy to preferentially deposit on the surface of the negative electrode current collector. When the current collector is a porous material, the deposition layer preferentially deposited on the surface of the current collector will hinder the metal ions from entering the pores inside the current collector, resulting in low pore utilization and easy formation of dendrites. After the affinity material is formed in the pores, this problem can be significantly improved. After the first charge, the metal preferentially migrates into the pores of the negative electrode current collector and combines with the affinity material to evenly form a metal composite material. In the subsequent charging process, the metal ions in the electrolyte preferentially diffuse and deposit on the metal composite material in the pores of the current collector to form a deposition layer, which improves the uniformity of the deposition layer and helps to improve the stability and safety of the battery.

[0084] According to some embodiments of the present application, the negative electrode of the secondary battery may also be a traditional negative electrode structure, specifically including a negative electrode current collector and a negative electrode film layer disposed on the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0085] The specific type of negative electrode active material is not limited, and active materials that can be used for the negative electrode of a secondary battery known in the art can be used, and those skilled in the art can make a selection according to actual needs. As an example, the negative electrode active material may include, but is not limited to, one or more of silicon-based materials, silicon-carbon materials, carbon materials, and selenium-based materials. Specifically, it includes one or more of artificial graphite, natural graphite, hard carbon, soft carbon, silicon-based materials and tin-based materials. Silicon-based materials can be selected from one or more of elemental silicon, silicon oxide compounds (such as silicon monoxide), silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Selenium-based materials can be selected from one or more of elemental selenium, selenium oxide compounds, and selenium alloys. These materials can all be obtained through commercial channels.

[0086] Negative electrode active materials can reduce negative electrode impedance, increase electrode capacity, and reduce abnormal precipitation of metallic sodium. Sodium metal easily intercalates and deintercalates into these negative electrode active materials. During the battery's charge and discharge cycles, the active material's structure undergoes minimal changes, extending the battery's lifespan.

[0087] In some embodiments, to further increase the energy density of the battery, the negative electrode active material may include a silicon-based material.

[0088] The negative electrode film layer usually optionally includes a binder, a conductive agent and other optional auxiliary agents.

[0089] As an example, the conductive agent may be one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0090] As an example, the binder may be one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).

[0091] As an example, other optional auxiliary agents may be thickening and dispersing agents (such as sodium carboxymethyl cellulose CMC-Na), and PTC thermistor materials.

[0092] The operating principle of this secondary battery is the intercalation and deintercalation of metal cations in an electrolyte salt. For example, when the battery is charging, the sodium ions are intercalated from the positive electrode, passing through the separator in the electrolyte, and intercalating into the negative electrode active material. Simultaneously, electrons flow from the positive electrode to the negative electrode in an external circuit. When the battery is discharging, the sodium ions are intercalated from the negative electrode active material, passing through the separator in the electrolyte, and intercalating into the positive electrode. Simultaneously, electrons flow from the negative electrode to the positive electrode in an external circuit.

[0093] For the secondary battery, the presence of the affinity material is also conducive to guiding the metal ions to preferentially enter the pores of the current collector porous material to complete embedding, thereby improving the pore utilization rate and improving the stability and safety of the secondary battery.

[0094] The secondary battery also includes a positive electrode sheet, which generally includes a positive electrode current collector and a positive electrode film layer disposed on the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0095] The positive electrode current collector may be a conventional metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the positive electrode current collector may be an aluminum foil.

[0096] There is no limitation on the specific type of the positive electrode active material. Active materials known in the art that can be used for the positive electrode of a secondary battery can be used. Those skilled in the art can select according to actual needs.

[0097] As an example, the positive electrode active material may include, but is not limited to, one or more of lithium transition metal oxides, lithium phosphates with an olivine structure and their respective modified compounds, transition metal oxides, polyanionic compounds, and Prussian blue analogs. Examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds. Examples of lithium phosphates with an olivine structure may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their modified compounds. These materials can all be obtained through commercial channels.

[0098] The modified compounds of the above materials may be doping-modified and / or surface-coated modified materials.

[0099] The positive electrode film layer usually optionally includes a binder, a conductive agent and other optional additives.

[0100] As an example, the conductive agent may be one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, Super P (SP), graphene, and carbon nanofibers.

[0101] As an example, the binder can be one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).

[0102] As an example, other optional auxiliary agents may be thickening and dispersing agents (such as sodium carboxymethyl cellulose CMC-Na), and PTC thermistor materials.

[0103] In some embodiments, the positive electrode current collector includes a porous material, including: a substrate, the substrate includes a porous material; an affinity material is also provided in the pores of the porous material, and the affinity material is used to promote the deposition of metal ions in the electrolyte.

[0104] The secondary battery further includes an electrolyte. According to some embodiments of the present application, the electrolyte includes metal ions, and the metal ions include at least one of sodium ions or lithium ions.

[0105] Sodium or lithium ions in the electrolyte can undergo a deposition-stripping or embedding-de-embedding process on the negative electrode current collector. Lithium ions, in particular, have a high nucleation overpotential on conventional porous current collectors, making them more likely to preferentially deposit on the porous surface. The use of the aforementioned affinity materials can significantly improve this issue, enhancing the cycling performance and safety of lithium metal secondary batteries.

[0106] Secondary batteries also include a separator, which is placed between the positive and negative electrodes. As an insulating layer, it effectively prevents contact between the positive and negative electrodes, which could cause internal short circuits, while allowing electrolyte ions to pass smoothly. The performance of the separator determines the secondary battery's interface structure and internal resistance, directly affecting the battery's mechanical strength and safety.

[0107] The specific type of separator material is not limited. Materials known in the art for use in secondary battery separators can be used, and those skilled in the art can select materials based on their needs. For example, separator materials can include, but are not limited to, one or more of polyolefins, fluoropolymers, cellulose, and glass fiber. Polyolefins can include, but are not limited to, one or more of polypropylene and polyethylene. These materials are commercially available.

[0108] In some embodiments, in some embodiments, the isolation membrane includes a base membrane and a coating located on one side / both sides of the base membrane, and the coating includes a filler. The filler may include an inorganic material, a polymer adhesive, and a dispersant. The inorganic material includes one or more of boehmite and silica, and the polymer adhesive material includes one or more of PVDF (polyvinylidene fluoride) and polystyrene-acrylate; the dispersant material includes polyvinyl alcohol, etc. By providing a coating on one side / both sides of the isolation membrane, the performance of the isolation membrane can be improved and regulated. The performance of the isolation membrane can be regulated by regulating the type of filler. For example, a filler with heat insulation and heat resistance can be added to improve the heat resistance of the isolation membrane. The specific type of the base membrane material is not limited and can include, but is not limited to, one or more of polyethylene, polypropylene and glass fiber. These materials can be obtained through commercial channels.

[0109] The embodiment of the present application has no particular limitation on the shape of the secondary battery, which can be cylindrical, square, or any other shape. As shown in FIG1 , a secondary battery 100 with a square structure is used as an example. FIG1 is a schematic structural diagram of some embodiments of the secondary battery 100 of the present application.

[0110] In some embodiments, the secondary battery 100 of the present application includes a housing 10 and a battery cell 20, and the battery cell 20 is accommodated in the housing 10. Please refer to Figure 2, which is a schematic diagram of the exploded structure of some embodiments of the secondary battery 100 of the present application. The housing 10 is used to provide a storage space for the battery cell 20, and the housing 10 can adopt a variety of structures. In some embodiments, the housing 10 may include a first part 11 and a second part 12, and the first part 11 and the second part 12 cover each other, and the first part 11 and the second part 12 jointly define a storage space for accommodating the battery cell 20. The second part 12 can be a hollow structure with one end open, and the first part 11 can be a plate-like structure, and the first part 11 covers the open side of the second part 12, so that the first part 11 and the second part 12 jointly define a storage space; the first part 11 and the second part 12 can also be hollow structures with one side open, and the open side of the first part 11 covers the open side of the second part 12. Of course, the box body 10 formed by the first part 11 and the second part 12 can be in various shapes, such as a cylinder, a cuboid, etc.

[0111] In the secondary battery 100, there may be multiple battery cells 20, which may be connected in series, in parallel, or in a hybrid configuration. A hybrid configuration refers to a combination of series and parallel configurations within the battery cells 20. Multiple battery cells 20 may be directly connected in series, in parallel, or in a hybrid configuration, and then the entire battery cell 20 may be housed within the housing 10. Alternatively, the secondary battery 100 may be constructed by first connecting multiple battery cells 20 in series, in parallel, or in a hybrid configuration to form a battery module, which is then connected in series, in parallel, or in a hybrid configuration to form a single unit housed within the housing 10. The secondary battery 100 may also include other structures, such as a busbar assembly for electrically connecting the multiple battery cells 20.

[0112] Each battery cell 20 may be a secondary battery, such as a lithium-ion battery, a sodium-ion battery, a magnesium-ion battery, or an aluminum-ion battery, but is not limited thereto. The battery cell 20 may be cylindrical, flat, rectangular, or have other shapes.

[0113] Battery manufacturing methods include laminated and wound types. Laminated batteries offer uniform current collection, low internal resistance, and high specific power. However, to ensure accuracy, they require extremely high mold precision, high equipment investment, and a complex process, resulting in low production efficiency. Wound batteries are simple to manufacture, with moderate equipment precision requirements during the production and assembly processes. They offer high production efficiency and low costs. In terms of performance, wound batteries offer excellent high and low temperature performance, very fast charging, an extremely long lifespan, a stable high output voltage, a sturdy structure, and strong shock resistance.

[0114] Please refer to Figure 3, which is a schematic diagram of the exploded structure of a battery cell 20 in some embodiments of the present application. A battery cell 20 is the smallest unit that makes up a battery. As shown in Figure 3, a battery cell 20 includes an end cap 21, a housing 22, an electrode assembly 23, and other functional components.

[0115] The end cap 21 is a component that covers the opening of the housing 22 to isolate the internal environment of the battery cell 20 from the external environment. The shape of the end cap 21 can be adapted to the shape of the housing 22 to fit the housing 22. Optionally, the end cap 21 can be made of a material with a certain hardness and strength (such as an aluminum alloy). This prevents the end cap 21 from deforming when subjected to compression or collision, thereby providing the battery cell 20 with greater structural strength and improved safety. The end cap 21 can be provided with functional components such as electrode terminals 21a. The electrode terminals 21a can be used to electrically connect to the electrode assembly 23 for inputting or outputting electrical energy from the battery cell 20. In some embodiments, the end cap 21 can also be provided with a pressure relief mechanism for relieving internal pressure when the internal pressure or temperature of the battery cell 20 reaches a threshold. The end cap 21 can also be made of a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and this embodiment of the present application does not impose any particular limitations on this. In some embodiments, an insulating member may be provided inside the end cap 21 to isolate the electrical connection components in the housing 22 from the end cap 21 to reduce the risk of short circuit. For example, the insulating member may be made of plastic, rubber, or the like.

[0116] The housing 22 is a component that cooperates with the end cap 21 to form the internal environment of the battery cell 20. This internal environment can be used to accommodate the electrode assembly 23, electrolyte, and other components. The housing 22 and end cap 21 can be separate components. An opening can be provided in the housing 22, and the end cap 21 is placed over the opening to form the internal environment of the battery cell 20. Alternatively, the end cap 21 and housing 22 can be integrated. Specifically, the end cap 21 and housing 22 can form a common connection surface before other components are inserted into the housing. When the interior of the housing 22 needs to be enclosed, the end cap 21 is placed over the housing 22. The housing 22 can have a variety of shapes and sizes, such as a rectangular parallelepiped, a cylindrical shape, or a hexagonal prism. Specifically, the shape of the housing 22 can be determined based on the specific shape and size of the electrode assembly 23. The housing 22 can be made of a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and this embodiment of the present application does not impose any particular limitations on this.

[0117] The electrode assembly 23 is a component in the battery cell 20 where electrochemical reactions occur. One or more electrode assemblies 23 may be contained in the housing 22. The electrode assembly 23 is mainly formed by winding or stacking positive and negative electrode sheets, and a separator is usually provided between the positive and negative electrode sheets. The parts of the positive and negative electrode sheets with active materials constitute the main body of the electrode assembly, and the parts of the positive and negative electrode sheets without active materials each constitute a tab 23a. The positive and negative electrode tabs may be located together at one end of the main body or respectively at both ends of the main body. During the charge and discharge process of the battery, the positive electrode active material and the negative electrode active material react with the electrolyte, and the tabs 23a connect the electrode terminals to form a current loop.

[0118] The electrolyte and secondary battery disclosed in the embodiments of the present application can be used in electrical devices that use secondary batteries as power sources or various energy storage systems that use secondary batteries as energy storage elements. The electrical devices can be, but are not limited to, mobile phones, tablets, laptops, electric toys, power tools, battery cars, electric cars, ships, spacecraft, and the like. Among them, electric toys can include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, and the like, and spacecraft can include airplanes, rockets, space shuttles, and spacecraft, and the like.

[0119] The energy storage system can be a hydropower, thermal, wind power, solar power station or other energy storage power supply system.

[0120] For the convenience of description, the following embodiments are described by taking a vehicle 1000 as an example of an electrical device according to an embodiment of the present application.

[0121] Please refer to Figure 4, which is a schematic structural diagram of a vehicle 1000 in some embodiments of the present application. The vehicle 1000 can be a fuel vehicle, a gas vehicle or a new energy vehicle. The new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A secondary battery 100 is provided inside the vehicle 1000, and the secondary battery 100 can be provided at the bottom, head or tail of the vehicle 1000. The secondary battery 100 can be used to power the vehicle 1000. For example, the secondary battery 100 can serve as an operating power source for the vehicle 1000. The vehicle 1000 can also include a controller 200 and a motor 300. The controller 200 is used to control the secondary battery 100 to power the motor 300, for example, for starting, navigating and driving the vehicle 1000.

[0122] In some embodiments of the present application, the secondary battery 100 can serve not only as an operating power source for the vehicle 1000 , but also as a driving power source for the vehicle 1000 , replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000 .

[0123] The current collector of the secondary battery in the aforementioned electrical device and energy storage system includes a substrate comprising a porous material; an affinity material disposed within the pores of the porous material, the affinity material being used to promote the deposition of metal ions in the electrolyte; the affinity material comprising at least one of a carbon-based material, a non-metallic oxide, a carbide, a fluoride, a nitride, a sulfide, a phosphide, and an organic material. This affinity material can effectively reduce the nucleation overpotential of metal ions on the porous current collector material, promote uniform diffusion and deposition of metal ions within the pores of the porous current collector material, inhibit the formation of dendrites, and enhance the cycling performance and safety of the secondary battery, thereby improving the operational stability and safety of the aforementioned electrical device and energy storage system.

[0124] The above-mentioned electrical devices and energy storage systems are also within the protection scope of this application.

[0125] The present application also provides a method for preparing a current collector, which is used to prepare the aforementioned current collector.

[0126] According to some embodiments of the present application, please refer to FIG5 , which is a schematic flow chart of an embodiment of a method for preparing a current collector of the present application, the preparation method comprising:

[0127] S101: providing a substrate, wherein the substrate comprises a porous material.

[0128] S102: forming an affinity material in the pores of the porous material to obtain a current collector.

[0129] Affinity materials can be formed in the pores of porous materials by vapor deposition, electroplating, etc.

[0130] As previously mentioned, the affinity material includes at least one of a carbon-based material, a non-metallic oxide, a carbide, a fluoride, a nitride, a sulfide, a phosphide, and an organic material. The current collector formed by this method contains the affinity material, allowing metal ions in the electrolyte to be uniformly deposited within the pores of the porous material, reducing the formation of dendrites and improving the cycle performance and safety of the secondary battery.

[0131] According to some embodiments of the present application, please refer to FIG6 , which is a flow chart of another embodiment of a method for preparing a current collector of the present application, the preparation method comprising:

[0132] S201: providing a substrate, wherein the substrate comprises a porous material.

[0133] S202: forming an affinity material on the porous material by vapor deposition;

[0134] S203: forming an insulating layer on the surface of the porous material to cover the affinity material on the surface of the porous material.

[0135] A more uniform affinity material can be formed by vapor deposition, thereby facilitating uniform deposition of metal ions in the electrolyte on the affinity material. According to some embodiments of the present application, affinity materials can also be formed on porous materials using methods other than vapor deposition, such as electroplating.

[0136] Because the insulating layer has a weak affinity with metal ions, by forming an insulating layer on the surface of the porous material, the metal ions can be inhibited from preferentially depositing on the surface of the current collector, further promoting the metal ions to preferentially deposit in the pores of the porous material, thereby reducing the generation of dendrites.

[0137] Below, the current collector and the method for preparing the current collector are described using Li (lithium) ion batteries as an example and in combination with specific embodiments. Those skilled in the art will understand that the current collector and the method for preparing the current collector described in this application are only examples, and any other suitable preparation method is within the scope of this application.

[0138] Example 1:

[0139] 1) Purchase commercially available foam copper with a thickness of 171 μm, a porosity of 72%, and an average pore size of 165 μm.

[0140] The foam copper sample was placed in a vacuum magnetron sputtering device to deposit magnesium (Mg). The vacuum magnetron sputtering device was set to an upper pressure limit of 0.8 MPa. A quartz microbalance was placed under the substrate in the chamber. After the sputtering started, the sputtering amount was controlled by measuring the weight of the substrate. A magnesium target was used to deposit 2.0 g / cm 2 The coating was formed to obtain a PVD-Mg20 copper foam sample.

[0141] 2) Immerse the PVD-Mg20 copper foam sample in 1 mol / L HCl (hydrochloric acid) for 15 seconds to remove the surface oxide layer. The sample is then rinsed with deionized water and anhydrous ethanol. Acid washing removes the oxide layer on the surface of the affinity material, improves its affinity for metal ions in the electrolyte, and increases deposition sites.

[0142] 3) The sample in 2) was taken out and dried in an oven at 60° C. for 10 min to obtain a PVD-Mg20 lithiophilic three-dimensional copper foam current collector.

[0143] Embodiment 2, 3:

[0144] The preparation method was the same as that in Example 1 except that the plating amount of the affinity material Mg was changed.

[0145] Examples 4 to 6:

[0146] Change the affinity material to Zn, and the affinity material plating amount is 2.0g / cm 2 , 2.5g / cm 2 and 3.0g / cm 2, the other preparation methods are the same as those in Example 1.

[0147] Examples 7 to 9:

[0148] Change the affinity material to Sn, and the affinity material plating amount is 2.0g / cm 2 , 2.5g / cm 2 and 3.0g / cm 2 , the other preparation methods are the same as those in Example 1.

[0149] Comparative Example 1:

[0150] The copper foam was replaced with a blank copper foam without affinity material, and the rest was the same as in Example 1.

[0151] Comparative Examples 2 to 4:

[0152] The pickling time was changed to 5s, 30s and 60s respectively, and the other preparation methods were the same as those in Example 2.

[0153] Example 10:

[0154] The copper foam was cut into small discs with a diameter of 18 mm, and then placed in a CVD (chemical vapor deposition) tube furnace, heated at 900 ° C for 10 minutes in a mixed flow of C2H2 (acetylene) and Ar (argon) with a flow rate of 100 / 10 sccm, and cooled while still passing the gas.

[0155] Example 11

[0156] The copper foam was cut into small discs with a diameter of 18 mm. The copper foam was then immersed in a mixed solution of 15 mL of 0.13 M (NH₄)₂S₂O₄ (ammonium persulfate) and 15 mL of 2.67 M NaOH (sodium hydroxide) for 10 minutes, removed, rinsed, and dried. The foam was then heated in a CVD tube furnace at 350°C for 1 hour in an Ar / NH₃ (ammonia) mixed flow at a flow rate of 100 / 50 sccm, and then cooled, with air introduced during cooling.

[0157] Example 12

[0158] The copper foam was cut into small discs with a diameter of 18 mm. The copper foam was then immersed in a mixture of 15 mL of 0.13 M (NH₄)₂S₂O₄ and 15 mL of 2.67 M NaOH for 10 minutes, removed, rinsed, and dried. The foam was then heated in a CVD tube furnace at 350°C for 1 hour in an Ar / NH₃ mixed flow at a flow rate of 100 / 50 sccm, and then cooled while still aerating the gas.

[0159] Example 13

[0160] The copper foam was cut into small discs with a diameter of 18 mm. The copper foam was then immersed in a mixture of 15 mL of 0.13 M (NH₄)₂S₂O₂ and 15 mL of 2.67 M NaOH for 10 minutes. The foam was then removed and immersed in a 5 M aqueous solution of Na₂S (sodium sulfide) for 4 hours. The sample was then washed and dried.

[0161] Example 14

[0162] Cut the copper foam into 18mm diameter discs and place them in two porcelain boats with 100mg of NaH2PO2 (sodium hypophosphite). Place the two boats in the center of a CVD tube furnace and flow argon. Place the boat containing NaH2PO2 near the inlet pipe. Heat at 300°C for 10 minutes.

[0163] Example 15

[0164] Cut the copper foam into 18mm diameter discs and place them in two porcelain boats with 100mg of PTFE (polytetrafluoroethylene). Place the two boats in the center of a CVD tube furnace and flow argon. Place the boat containing the PTFE near the inlet pipe. Heat at 300°C for 10 minutes.

[0165] Example 16

[0166] The copper foam was cut into small discs with a diameter of 18 mm and immersed in 40 mL of a 1:1 mixture of DI water and ethanol containing 0.5 g of C6H5N3 (3-amino-6-cyanopyridine). The mixture was heated at 60°C for 1 hour. Then, 40 mL of a solution containing 0.4 mL of aniline was added. After heating for a further 15 minutes, 15 mL of a mixture of 5.3% ammonium sulfate and 1 M HCl was added dropwise. Heating continued for 2 hours. The sample was then washed and dried.

[0167] Test Method

[0168] 1. Overpotential (nucleation overpotential) test method:

[0169] 1) A discharge test was performed using a button cell battery. The positive electrode of the battery used the gradient lithium-philic three-dimensional current collector obtained in the examples and comparative examples, the negative electrode used a lithium sheet, the electrolyte used 1 M LiFSI (lithium bis(trifluoromethanesulfonyl)imide) dissolved in DME (dimethyl ether), and the isolation membrane used a 12 μm PE (polyethylene) film.

[0170] 2) Discharge conditions: The half-cell is discharged at a constant current at room temperature with a current density of 1 mA / cm2. The difference between the lowest voltage point and the stable discharge voltage is the nucleation overpotential.

[0171] 2. (Current Collector / Li Half-Cell) Short-Circuit Time Test Method:

[0172] 1) A discharge test was performed using a button cell battery. The positive electrode of the battery used the gradient lithium-philic three-dimensional current collector obtained in the examples and comparative examples, the negative electrode used a lithium sheet, the electrolyte used 1 M LiFSI (lithium bis(trifluoromethanesulfonyl)imide) dissolved in DME (dimethyl ether), and the isolation membrane used a 12 μm PE (polyethylene) film.

[0173] 2) Discharge conditions: The half-cell is discharged at a constant current at room temperature with a current density of 1 mA / cm 2 , continue discharging until a short circuit signal appears, that is, the battery voltage jumps to 0V.

[0174] 3) Record the time from the start of discharge to short circuit.

[0175] 3. Test methods for initial CE, average CE, and (LFP / current collector) full battery cycle 50% capacity retention cycles:

[0176] CE stands for Coulombic efficiency (CE), which is the ratio of a battery's discharge capacity to its charge capacity during the same cycle. Initial CE = initial discharge capacity / initial charge capacity. Average CE is the average of discharge capacity / charge capacity over multiple cycles.

[0177] LFP is the abbreviation of LiFePO4, which is lithium iron phosphate, an electrode material for lithium-ion batteries.

[0178] 1) A cycle test was performed using a button cell battery. The positive electrode of the battery used lithium iron phosphate, wherein the lithium iron phosphate: conductive carbon black: PVDF (polyvinylidene fluoride) binder was 8:1:1. The negative electrode used the gradient lithium-philic three-dimensional current collector obtained in the examples and comparative examples. The electrolyte used 1 M LiFSI dissolved in DME, and the isolation membrane used a 12 μm PE film.

[0179] 2) Charging Conditions: The battery was charged at room temperature using the constant current-constant voltage (CC-CV) mode. First, charge at a fixed rate of 0.2C in the constant current mode until the voltage reached 3.65V. Then, switch to the constant voltage mode with a cutoff current of 0.05C to fully charge the battery.

[0180] 3) Discharge conditions: Discharge in constant current mode at a discharge rate of 0.5C to 2V and cycle for 200 cycles.

[0181] 4) Obtain the value of the first discharge capacity / first charge capacity to obtain the first efficiency CE;

[0182] 5) Obtain the discharge capacity / charge capacity values ​​after 200 cycles and calculate the average CE;

[0183] 6) Obtain and record the number of cycles when the full battery cycle reaches 50% capacity, and obtain the (LFP / current collector) full battery cycle 50% capacity retention cycle number.

[0184] Please refer to Table 1 for specific current collector materials, preparation processes, and performance test results.

[0185] Table 1: Preparation process parameters and performance test results of Examples 1-9 and Comparative Examples 1-4

[0186] Among them, in Table 1, the meaning of the collector names of Examples 1-9 and Comparative Examples 2-4 is: affinity material preparation method + affinity material type + affinity material plating amount + porous material type. For example, in Example 1, the current collector name "PVD-Mg20 foam copper" means: the affinity material is formed by PVD (physical vapor deposition) process, the affinity material type is metal Mg, the coating amount of the affinity material is 2.0 g / cm2, and the porous material type is foam copper.

[0187] The names of the current collectors in Examples 10-16 mean: foam copper + affinity material type. For example, in Example 10, the name of the current collector "Cu@C" means: foam copper + carbon-based affinity material. In Example 16, the name of the current collector "Cu@PANI" means: foam copper + polyaniline affinity material.

[0188] Result Analysis

[0189] 1. For Comparative Example 1, where the current collector is blank copper foam, it can be seen that its (current collector / Li half-cell) short-circuit time is only 159h, and the (LFP / current collector) full battery cycle 50% capacity retention cycle is only 66h, and the battery performance is poor. For the deposition effect of lithium ions on it, please refer to Figure 7, which is a morphology diagram of the current collector of Comparative Example 1 of this application under an optical microscope test, where 1 is a lithium deposition layer, 2 is a copper foam skeleton, and 3 is a pore in the copper foam. Lithium nucleates locally on the copper foam skeleton 2, showing obvious agglomeration. There are a large number of areas on the copper foam skeleton 2 that are not covered by lithium. The uniformity of the lithium deposition layer 1 is low, and it is preferentially deposited on the surface of the copper foam skeleton 2, and the pores 3 are blocked.

[0190] 2. Compared with Comparative Example 1, the values ​​of (current collector / Li half-cell) short-circuit time and (LFP / current collector) full battery cycle 50% capacity retention cycle in Examples 1 to 9 are relatively high, indicating that the lithium nucleation overpotential of the copper foam with affinity material is reduced compared with the blank copper foam, and the cycle performance is improved.

[0191] 3. Comparing Examples 1 to 6 with Examples 7 to 9, the values ​​of the (current collector / Li half-cell) short-circuit time and the (LFP / current collector) full battery cycle 50% capacity retention cycle times of the former are relatively higher, indicating that when the affinity material uses Mg and Zn, the effect of improving the battery cycle performance is better than when the affinity material uses Sn.

[0192] 4. Comparing Examples 1 to 3 with Examples 4 to 6, the values ​​of the (current collector / Li half-cell) short-circuit time and the (LFP / current collector) full battery cycle 50% capacity retention cycle of the former are relatively higher, indicating that the affinity material Mg has a better improvement effect than Zn.

[0193] The morphology of Examples 2, 5, and 8 can refer to Figures 8-10, wherein Figure 8 is a morphology of the optical microscope test of the current collector of Example 8 of the present application; Figure 9 is a morphology of the optical microscope test of the current collector of Example 5 of the present application; Figure 10 is a morphology of the optical microscope test of the current collector of Example 2 of the present application. It can be observed from Figure 8 that when the affinity material is Sn, although Li has been uniformly deposited in the pores 3 of the foam copper skeleton (not shown in the figure, the foam copper skeleton is covered by the lithium deposition layer 1), a mossy lithium deposition layer 1 is formed, i.e., mossy lithium, which has a safety hazard. It can be observed from Figure 9 that when the affinity material is Zn, because Li has a certain solid solubility (maximum content of solute in the solid solution) in the Li-Zn alloy, the lithium deposition layer 1 is more uniformly deposited in the pores 3 of the foam copper skeleton (not shown in the figure, the foam copper skeleton is covered by the lithium deposition layer 1), and is more adherent to the foam copper skeleton, reducing the mossy lithium, but the surface of the lithium deposition layer 1 is still relatively rough. It can be observed from Figure 10 that when the affinity material is Mg, the solid solubility of Li in the alloy is higher, the surface roughness of the lithium deposition layer 1 is greatly reduced, and it is evenly deposited in the pores 3 of the foam copper skeleton (not shown in the figure, the foam copper skeleton is covered by the lithium deposition layer 1). Correspondingly, its performance test results are the best in Examples 1-9.

[0194] 5. Compared with Examples 1 and 3, the values ​​of (current collector / Li half-cell) short-circuit time and (LFP / current collector) full battery cycle 50% capacity retention cycle are relatively high, indicating that when the affinity material coating amount is 2.5g / cm 2 The improvement effect is best.

[0195] 6. In Example 2, compared with Comparative Examples 2 to 4, the values ​​of the short-circuit time (current collector / Li half-cell) and the number of cycles in which the capacity of the full battery is maintained at 50% are relatively high. This indicates that when hydrochloric acid is used to pickle the copper foam with affinity material to remove the oxide layer, the pickling time is optimally 15 seconds. If the time is too short, the oxide layer may not be completely removed, and there will be fewer deposition active sites on the affinity material. If the time is too long, the oxide layer is completely removed, but part of the affinity material is dissolved, which also reduces the deposition active sites on the affinity material.

[0196] 7. Compared with Comparative Example 1, the values ​​of the short-circuit time (current collector / Li half-cell) and the number of cycles of 50% capacity retention in the full battery cycle (LFP / current collector) in Examples 10 to 16 are significantly improved, and the absolute value of the overpotential is reduced, indicating that the growth of a lithium-philic layer of carbon-based, oxide, nitride, sulfide, phosphide, fluoride, and organic molecules on the foam copper can be used as the negative electrode current collector of a negative electrode-free lithium metal battery, which can effectively reduce the nucleation overpotential of Li and improve the performance of the battery.

[0197] In summary, the present application provides a current collector, a secondary battery, an electrical device, and a method for preparing the current collector, wherein the current collector comprises: a substrate comprising a porous material; an affinity material disposed in the pores of the porous material, the affinity material being used to promote the deposition of metal ions in the electrolyte. Through the above-described method, the nucleation overpotential of metal ions on the porous material of the current collector can be effectively reduced, promoting the uniform diffusion and deposition of metal ions within the pores of the porous material of the current collector, inhibiting the formation of dendrites, and improving the cycle performance and safety of the secondary battery.

[0198] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A current collector, characterized in that: include: a substrate comprising a porous material; Affinity materials are arranged in the pores of the porous material, and the affinity materials are used to promote the deposition of metal ions in the electrolyte; The affinity material includes at least one of a carbon-based material, a non-metallic oxide, a carbide, a fluoride, a nitride, a sulfide, a phosphide and an organic material.

2. The current collector according to claim 1, characterized in that: The carbon-based material includes a heteroatom-doped carbon-based material.

3. The current collector according to claim 1 or 2, characterized in that: The carbon-based material comprises at least one of graphite, graphene, graphyne, hard carbon and derivatives thereof; and / or The carbon-based material includes at least one of nitrogen-doped graphyne, porous graphene and graphitized spherical carbon particles.

4. The current collector according to claim 1, characterized in that: The oxide comprises at least one of graphene oxide and its derivatives; And / or, the nitride comprises at least one of copper nitride, molybdenum nitride and derivatives thereof; and / or, the phosphide comprises at least one of copper sulfide, molybdenum sulfide and derivatives thereof; and / or, the fluoride comprises at least one of copper fluoride, nickel fluoride, magnesium fluoride and derivatives thereof; And / or, the organic material includes at least one of polyvinylidene fluoride, pyrrole, pyridine, polyaniline and derivatives thereof.

5. The current collector according to any one of claims 1 to 4, characterized in that: The affinity material also includes at least one of a metal material and a metal oxide.

6. The current collector according to claim 5, characterized in that: The metal material includes an element capable of forming an alloy with metal ions in the electrolyte; and / or, The metal material includes an element capable of forming a solid solution with metal ions in the electrolyte; and / or, The metal oxide includes at least one of copper oxide, zinc oxide, magnesium oxide, antimony oxide and derivatives thereof.

7. The current collector according to any one of claims 1 to 6, characterized in that: The metal ions in the electrolyte include at least one of lithium ions or sodium ions.

8. The current collector according to any one of claims 1 to 7, characterized in that: The coating amount of the affinity material is 2-3 g / cm 2 .

9. The current collector according to any one of claims 1 to 8, characterized in that: The thickness of the affinity material is 2-20 μm.

10. The current collector according to any one of claims 1 to 9, characterized in that: The porous material includes one or more of foamed copper and dealloyed porous copper.

11. The current collector according to any one of claims 1 to 10, characterized in that: The pore size of the porous material is 5-500 μm, and the porosity is 30%-70%.

12. A secondary battery, characterized in that: The invention comprises a negative electrode, wherein the negative electrode comprises the current collector according to any one of claims 1 to 11.

13. The secondary battery according to claim 12, characterized in that: The secondary battery is a negative electrode-free secondary battery.

14. The secondary battery according to claim 12 or 13, characterized in that: The secondary battery further includes an electrolyte, the electrolyte includes metal ions, and the metal ions include at least one of sodium ions or lithium ions.

15. An electrical device, characterized in that: Comprising the secondary battery as claimed in any one of claims 12 to 14.

16. A method for preparing a current collector, characterized in that: providing a substrate, the substrate comprising a porous material; Affinity material is formed in the pores of the porous material to obtain the current collector as claimed in any one of claims 1 to 11.

17. The method for preparing the current collector according to claim 16, characterized in that: forming an affinity material on the porous material by vapor deposition; An insulating layer is formed on the surface of the porous material to cover the affinity material on the surface of the porous material.